Respuesta :
[tex]\dfrac{12y^7}{18y^{-3}} = \dfrac{2y^{7+3}}{3} = \dfrac{2y^{10}}{3} = \dfrac{2}{3}y^{10} [/tex]
The simplified form will be [tex]\dfrac{2}{3} y^{10}[/tex].
Given expression,
[tex]\dfrac{12y^7}{18y^{-3}}[/tex].
We have to simplify the given expression.
Now, simplification means to represent the variable in minimum power and to make the fraction simple.
So, applying the identity, [tex]\dfrac{x^{m} }{x^{n} } }=x^{m-n}[/tex] we get,
[tex]\dfrac{12y^7}{18y^{-3}}=\dfrac{12}{18} \times y^{7-(-3)}[/tex]
[tex]\dfrac{12y^7}{18y^{-3}}=\dfrac{12}{18} \times y^{7+3}[/tex]
[tex]\dfrac{12y^7}{18y^{-3}}=\dfrac{2}{3} \times y^{10}[/tex]
Hence the simplified form of [tex]\dfrac{12y^7}{18y^{-3}}[/tex] is [tex]\dfrac{2}{3} \times y^{10}[/tex].
For more details on simplification follow the link:
https://brainly.com/question/12616840